Structural model of the full-length Ser/Thr protein kinase StkP from S. pneumoniae and its recognition of peptidoglycan fragments. Issue 14 (26th October 2018) - Righino, Benedetta; Galisson, Frédéric; Pirolli, Davide; Vitale, Serena; Réty, Stéphane; Gouet, Patrice; De Rosa, Maria Cristina
Abstract : The unique eukaryotic-like Ser/Thr protein kinases of Streptococcus pneumoniae, StkP, plays a primary role in the cell division process. It is composed of an intracellular kinase domain, a transmembrane helix and four extracellular PASTA subunits. PASTA domains were shown to interact with cell wall fragments but the key questions related to the molecular mechanism governing ligand recognition remain unclear. To address this issue, the full-length structural model of StkP was generated by combining small-angle X-ray scattering data with the results of computer simulations. Docking and molecular dynamics studies on the generated three-dimensional model structure reveal the possibility of peptidoglycan fragment binding at the hinge regions between PASTA subunits with a preference for a bent hinge between PASTA3 and PASTA4.